Cyber Threat Mitigation of Wireless Sensor Nodes for Secured, Trustworthy IoT Services. Issue 1 (2nd July 2016) - Chaudhuri, Abhik
Abstract: This article discusses about the potential of the Internet of Things technology (IoT), the IoT-enabled services in smart cities, wireless sensor nodes as key components to deliver the smart services, security threats of wireless sensor nodes and how we can mitigate these threats with assurance to provide secured and trustworthy smart services.